Case Report: A Novel Homozygous Frameshift Mutation of the SKIV2L Gene in a Trichohepatoenteric Syndrome Patient Presenting With Short Stature, Premature Ovarian Failure, and Osteoporosis - Yang, Minyi; Jiang, Yu; Shao, Xinyu (Frontiers in Genetics, 2022)
Background: Trichohepatoenteric syndrome (THES) is a rare Mendelian autosomal recessive genetic disease characterized by intractable diarrhea, woolly hair, facial abnormality, immune dysfunction, and intrauterine growth restriction. THES mutations are found in the TTC37 and SKIV2L genes, which encode two components of the human superkiller (SKI) complex. Methods and results: We report one case of a 32-year-old woman of Chinese descent with THES, who was born with a low weight (2000 g). She had intractable diarrhea during the neonatal period and was allergic to cow’s milk and condensed milk, but did not require total parenteral nutrition. She experienced menarche at age 12 and amenorrhea at age 28. In May 2019, the patient presented with a left fibular head fracture and was diagnosed with osteoporosis. Genetic testing showed a novel mutation in exon1 (p.E5Afs*37 (c.12_13del)) of SKIV2L, which is composed of 28 exons. After the diagnosis, hormone replacement therapy was prescribed, in addition to the routine calcium and vitamin D supplements. Conclusion: This case expands the clinical characteristic and phenotype spectrum of THES, providing further understanding of SKIV2L and its autoimmune influence.